Clinical Characteristics and Manifestations of Fungal Esophagitis: A Single-Center Experience in South China - Shu-Kai Zhan; Xiao-Qin Wu; Feng-Ping Zheng (Gastroenterology Research and Practice)
Fungal esophagitis is a common infectious disease, although the pathogenic clinical characteristics remain incompletely clear, especially in South China. The goal of this study was to investigate the pathogenic clinical characteristics of fungal esophagitis and the efficacy of different therapeutic strategies at a tertiary hospital in South China. A retrospective study was conducted from January 2007 to December 2017. Data from 113,390 patients who were treated in the endoscopic unit were retrieved and analyzed. To further understand the pathogen and risk factors for fungal esophagitis, we performed a case-control analysis of 101 patients and 202 controls. Of the 113,390 patients, 932 (0.82%) were positive. The annual detection rate ranged from 0.345% to 1.106%, showing an initially increasing and subsequently decreasing trend. The patients’ median age was 49 years (range from 8 to 85), and most were men (615/932, 65.99%). Candida albicans was found in samples collected from 36 patients, without any drug-resistant strains. Age (P=0.018), malignancy (OR=4.031, 95% CI: 1.562~10.407), cigarette smoking (OR=3.017, 95% CI: 1.645~5.533), and the use of antibiotics (OR=2.178, 95% CI: 1.078~4.400) or immunosuppressants (OR=6.525, 95% CI: 1.089~39.105) were independently associated with esophageal candidiasis. Fluconazole had a better curative effect than nystatin (OR=4.047, 95% CI: 1.282~12.772) or simple observation (OR=8.91, 95% CI: 2.61~30.49). In conclusion, fungal esophagitis primarily affects men and elderly individuals; it develops in the setting of malignancy, smoking, and certain previous medication use. Candida albicans is the most common pathogen and is sensitive to antifungal agents. Fluconazole has a good therapeutic effect.